1997
DOI: 10.1038/bjc.1997.236
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, tobacco and oesophageal cancer: effects of the duration of consumption, mean intake and current and former consumption

Abstract: Summary Numerous epidemiological studies have shown that alcohol and tobacco consumption are the main risk factors for oesophageal cancer in Western countries. In these studies, the consumption of both alcohol and tobacco has almost always been measured as current mean intake. The present case-control study investigates the association between alcohol and tobacco consumption and the risk of oesophageal cancer by assessing exposure as total lifetime intake, mean weekly intake, duration of consumption and former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 27 publications
7
59
1
3
Order By: Relevance
“…Another case-control study in France suggested that alcohol consumption and tobacco consumption influenced the risk of esophageal cancer in different ways. In the case of alcohol, the risk depended only on mean intake; however, with regard to smoking, the risk depended mainly on duration of consumption (Launoy et al, 1997). These results were almost in accordance with the results of our study for a prospective cohort.…”
Section: Discussionsupporting
confidence: 82%
“…Another case-control study in France suggested that alcohol consumption and tobacco consumption influenced the risk of esophageal cancer in different ways. In the case of alcohol, the risk depended only on mean intake; however, with regard to smoking, the risk depended mainly on duration of consumption (Launoy et al, 1997). These results were almost in accordance with the results of our study for a prospective cohort.…”
Section: Discussionsupporting
confidence: 82%
“…13,15,21,22 For drinking cessation no clear favorable effect was found, in those studies former drinkers were at a lower, 13,21 similar or even higher risk than current drinkers. 15,22 In our present study, quitting alcohol for 10 or more years and tobacco for 5 or more years were separately associated with a 70% and 60% risk reduction.…”
Section: Discussionmentioning
confidence: 88%
“…From a biological viewpoint, an apparent duration effect together with reduction of elevated risk after a relatively short time period of smoking cessation supports the hypothesis that tobacco contains both early-stage and late-stage carcinogens, as evaluated by IARC Monographs. 1 In contrast, the risk reduction after a long term of drinking cessation, as well as the inconsistent findings provided by earlier studies, 13,15,21,22 suggest that alcohol may not merely involve in a late-stage carcinogenesis of esophageal cancer, as proposed by IARC Monographs. 2 The practice of chewing of betel quid varies from country to country.…”
Section: Discussionmentioning
confidence: 98%
“…Tumorigenesis is a complicated process involving numerous factors, multiple steps and genetic as well as epigenetic alterations in various genes. The pathogenesis of ESCC has been mainly attributed to environmental factors, including malnutrition, smoking, alcohol use and inflammation (27)(28)(29). However, recent studies have revealed that genetic and Table V.…”
Section: Discussionmentioning
confidence: 99%